QUALITATIVE DRUG: WHAT SHOULD IT LOOK LIKE? - V. V. Iakusevich (Рациональная фармакотерапия в кардиологии)
Drug quality in modern market is discussed. There is an increase of a number of drugs that don’t meet to the quality requirements.Most of them are produced by Russian manufacturers, which number has also increased recently. According to official data 6-10%of all medicines are counterfeit. Quality reduction is also connected with a huge number (80%) of reproduced drugs (generics). Considerable part among generics doesn’t pass required evaluation of equivalence with original product. Approved deviations (according to Russian regulative rules) in pharmacological equivalence may reach 5%, and in pharmacokinetic equivalence -25%. Evidences of pharmacodynamic (therapeutic) equivalence are not required at all. At the same time, author advocates the production of qualitative generics that can providemodern and accessible treatment. Generic quality should be confirmed by randomized studies with cross-over designed comparison with original drug in parallel groups. The examples of the generics with such evidences are demonstrated. The requirements to the data about drugs are given to help the physician to make a right independent estimation of its quality.